A new potentially Endangered species of Megophrys (Amphibia: Megophryidae) from Mount Ky Quan San, north-west Vietnam. Issue 39 (17th October 2020) - Tapley, Benjamin; Cutajar, Timothy; Nguyen, Luan Thanh; Portway, Christopher; Mahony, Stephen; Nguyen, Chung Thanh; Harding, Luke; Luong, Hao Van; Rowley, Jodi J. L.
ABSTRACT: The genus Megophrys is known to harbour morphological cryptic species diversity. During field work on Vietnam's third highest peak, Mount Ky Quan San, north-west Vietnam, we collected specimens of a new species of Megophrys at two locations more than 2000 m above sea level (asl). Phylogenetic analyses using mitochondrial markers place the new species within the subgenus Panophrys, a primarily Chinese radiation within the genus Megophrys . We describe the species based on an all-male type series and distinguish it from all other Megophrys species from mainland Southeast Asia, north of the Isthmus of Kra and nearby provinces of China (Yunnan, Guangxi and Guizhou) based on morphological, molecular and bioacoustic data. The new species is inferred to form a clade along with M. hoanglienensis and M. fansipanensis ; it is syntopic with the former but has a non-overlapping range with the latter. Uncorrected p distances for the 16S rDNA and CO1 genes between the new species and closest relatives exceed values observed between other closely related species in the Panophrys subgenus. The new species is most similar to M. fansipanensis in terms of morphology, and several call parameters also overlap with this species; however, these two species call at different times of year. This is the fourth likely range-restricted and Endangered Megophrys species described from the Hoang Lien Range since 2017, and this discovery further highlights the significance of the Hoang Lien Range for Vietnam's amphibian diversity. http://zoobank.org/NomenclaturalActs/69340DD7-B21E-4DD0-836F-6741878013BB